AN ANALYTICAL STUDY OF SOCIO-ECONOMIC AND INFRASTRUCTURE DEVELOPMENT IN SOLU VILLAGE UNDER UNNAT BHARAT ABHIYAN - Shriram Kargaonkar,; Rahul Barathe,; Mangesh Bhople,; Reetuja Deshpande,; Sachin S. Zende,; Pandurang V. Thatkar, (The Bioscan, 2024)
This research paper offers an in-depth examination of the socio-economic conditions in Solu village from Pune district in Maharashtra aligning with the Unnat Bharat Abhiyan (UBA) initiative. It investigates critical demographic factors, access to basic amenities, agricultural practices, educational opportunities, and the implementation of government schemes within the village. By employing thorough data collection and analytical methods, the study uncovers significant disparities in resource accessibility and evaluates the effectiveness of existing government interventions. The findings reveal urgent areas that require attention, particularly in tackling poverty, improving health care, enhancing educational facilities, and upgrading infrastructure. These insights are particularly relevant to Sustainable Development Goals (SDGs), especially Goal 1 (No Poverty), Goal 3 (Good Health and Well-being), and Goal 4 (Quality Education). To promote sustainable development in Solu village, the paper offers actionable recommendations, including the introduction of targeted development programs and community engagement strategies. This study serves as a valuable resource for policymakers and development practitioners aiming to foster holistic growth and address socio-economic challenges effectively.